Radial tool wear analysis and compensation strategy for microhole arrays in sequential hybrid laser beam micromachining (LBMM) and micro‑EDM - Wan Azhar, Wan Ahmad; Saleh, Tanveer (Springer Nature, 2025)
Microhole arrays have significant applications across various industries, including aerospace, turbo machinery, industrial filtration, microfluidic devices, and biomedical engineering. Several methods exist for manufacturing microhole arrays, but the sequential hybrid laser beam micromachining (LBMM) and microelectrical discharge machining (μEDM) process offers complementary advantages, significantly reducing production time while achieving high precision. However, due tothe pre-existing tapered holes created by LBMM, tool wear during the subsequent μEDM process primarily occurs on the sides of the electrode, leading to more significant radial wear. Reusing the same electrode results in tapered holes, while frequent electrode replacement is impractical and costly. This study investigates the tool wear characteristics in the hybrid LBMM–μEDM process across different materials and thicknesses and proposes compensation strategies to improve machining consistency. Axial and radial tool wear lengths were characterized by machining 300-μm microhole arrays on 600 and 200-μm thick copper and stainless steel workpieces, with microscopic images of the electrode captured after each machining step. Analysis revealed that the hybrid LBMM–μEDM process resulted in more prominent radial tool wear length compared to the pure μEDM process, while the pure μEDM process exhibited higher axial tool wear length. Radial wear was more pronounced in stainless steel than in copper, and thicker workpieces increased axial wear. To address tapering, a compensation strategy was developed by adjusting the programmed depth based on radial wear, reducing the taper angle by 7 × . This approach enables the hybrid process to match the hole quality of pure μEDM while achieving a 4 × faster machining rate.